Temporal Distribution Of Arthropoda Types On Purchase (Portulaca oleracea L.) In Red Chillia Agricultural Land, Afdeling Ii Village Rantau Prapat, Bilah Barat District, Labuhanbatu Regency - Syukur Harahap; Yusmaidar Sepriani; Hilwa Walida; Khairul Rizal (International Journal of Science and Environment (IJSE), 2022)
The purpose of this study was to analyze and describe the temporal distribution of arthropods on purslane (Portulaca oleracea L.) on red chili farms, Afdeling II Village, West Bilah Subdistrict, Labuhanbatu Regency. This research method is descriptive exploratory research with a quantitative approach. This is to describe and analyze the temporal distribution of arthropods in purslane (Portulaca oleracea L.). Data was observed from the arrival of arthropods at a predetermined time, namely three 3 observation times, including: time I (07.00-08.00), time II (12.00-13.00), and time III (16.00-17.00) for 10 minutes. Each time the observation was repeated 4 times. The results of this study showed that the daily visits of arthropods at 12.00-13.00 were higher than the daily visits at 07.00-08.00 and 16.00-17.00. Each family of arthropods has a different level of daily visits at each time of arrival which is caused by internal factors (physiological, reproductive ability, life cycle, age) and external factors (physical factors, food, temperature and humidity). The daily visit frequency of this arthropod indicates that purslane (Portulaca oleracea L.) is a habitat for arthropods and can be used as a refugia plant.